Trois opinions sur l’évolution de l’assurance I.A.R.D. au Canada - collaborateurs, Divers (Assurances)

(untitled) (HEC Montréal, 1983)
ln the present articles, three views are presented with respect to the immediate future of insurance: the concentration of brokerage firms and its effects, general insurance in the next decade and lastly, the future of brokerage firms. While, on one hand, the articles represent three distinct works both in spirit and composition, on the other, each author has sought to focus upon the most important points of his subject matter. Insurance must evolve. Under what conditions will this evolution occur? The present studies may provide our readers an insight into the question and allow them to draw their own conclusion.